2021
DOI: 10.3390/jcm10153208
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Pressure as a Predictor of Success in Catheter Ablation of Atrial Fibrillation in a Real-Life Cohort

Abstract: Aims: The clinical role of the left atrial (LA) hypertension in patients with atrial fibrillation (AF) and its role as predictor in those undergoing pulmonary vein (PV) isolation is still unknown. The aim of the present study was to analyze the role of LA pressure in patients with nonvalvular AF who underwent PV isolation and its implication for AF catheter ablation. Methods: Consecutive patients with drug resistant AF who underwent PV isolation at San Maurizio Regional Hospital of Bolzano (Italy) as index pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Manfrin et al demonstrated that higher LA pressure was associated with an increased risk of AF recurrence after catheter ablation and identified a mean LA pressure of >15 mm Hg as the optimal cut‐off value. 12 Evranos et al showed that LA pressure >14 mm Hg carried a significant risk for AF recurrence after cryoablation. 10 In addition, Gilge et al reported an association between elevated LA pressure and heart failure occurrence after catheter ablation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Manfrin et al demonstrated that higher LA pressure was associated with an increased risk of AF recurrence after catheter ablation and identified a mean LA pressure of >15 mm Hg as the optimal cut‐off value. 12 Evranos et al showed that LA pressure >14 mm Hg carried a significant risk for AF recurrence after cryoablation. 10 In addition, Gilge et al reported an association between elevated LA pressure and heart failure occurrence after catheter ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive assessment of LA hypertension by speckle‐tracking echocardiography in patients with AF may have the potential to provide valuable information for the selection of optimal candidates for catheter ablation and periprocedural management, because LA hypertension carries a significant risk for AF recurrence. 10 , 12 Furthermore, central obesity and inflammation could be therapeutic targets of LA hypertension and possibly subsequent AF recurrence. Therapeutic intervention for central obesity might be able to decrease LA pressure through improvement of metabolic disorders and neurohumoral responses (ie, renin–angiotensin–aldosterone system and sympathetic nervous system).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results do apply to the subgroup of patients with out-of-the-box settings with fixed AV and VV delays; also, our results apply to a population of patients treated in the period 2013-2018 and it is possible that response to CRT in contemporary practice may be better thanks to the progressive use of quadripolar leads and AV optimization algorithms. We analyzed the occurrence of AF > 7 days as a function of PR interval, even if many factors may actually condition AF onset in patients with LV dysfunction and AF [2,27,[31][32][33][34][35]. Additionally, given the observational nature of the study, granular descriptions of specific echocardiographic measurements, such as grade and type of valvular heart disease, were missing.…”
Section: Study Limitationsmentioning
confidence: 99%